Effects of Adsorbate Coverage and Bond‐Length Disorder on the d‐Band Center of Carbon‐Supported Pt Catalysts. Issue 8 (13th March 2014) - Small, Matthew W.; Kas, Joshua J.; Kvashnina, Kristina O.; Rehr, John J.; Nuzzo, Ralph G.; Tromp, Moniek; Frenkel, Anatoly I.
Abstract Determination of the factors that affect the d‐band center of catalysts is required to explain their catalytic properties. Resonant inelastic X‐ray scattering (RIXS) enables direct imaging of electronic transitions in the d‐band of Pt catalysts in real time and in realistic environmental conditions. Through a combination of in situ, temperature‐resolved RIXS measurements and theoretical simulations we isolated and quantified the effects of bond‐length disorder and adsorbate coverage (CO and H2) on the d‐band center of 1.25 nm size Pt catalysts supported on carbon. We found that the decrease in adsorbate coverage at elevated temperatures is responsible for the d band shifts towards higher energies relative to the Fermi level, whereas the effect of the increase in bond‐length disorder on the d‐band center is negligible. Although these results were obtained for a specific case of non‐interacting support and weak temperature dependence of the metal–metal bond length in a model catalyst, this work can be extended to a broad range of real catalysts.